PR TECHNOLOGIES USED TO ADDRESS ENVIRONMENTAL PROBLEMS (Academicia Globe: Inderscience Research, 2022)
The article talks about the fact that the concept of pr arose on the basis of the political network, but today it has its own place in all spheres, in particular in the ecosystem. The concept of ecological pablik rileyshnz ("green pr") is one of the new, but topical areas of study, which is considered important in terms of human life, health, in other sectors.